Development and Psychometric Properties of the Sleep Parenting Scale for Infants. Issue 2 (3rd April 2023) - Lo, Brian K.; McTernan, Melissa L.; Haines, Jess; Savage, Jennifer S.; Kugler, Kari C.; Haneuse, Sebastien; Redline, Susan; Taveras, Elsie M.; Davison, Kirsten K.
Abstract: Although infants' sleep behaviors are shaped by their interactions with parents at bedtime, few tools exist to capture parents' sleep parenting practices. This study developed a Sleep Parenting Scale for Infants (SPS-I) and aimed to (1) explore and validate its factorial structure, (2) examine its measurement invariance across mothers and fathers, and (3) investigate its reliability and concurrent and convergent validity. SPS-I was developed via a combination of items modified from existing scales and the development of novel items. Participants included 188 mothers and 152 mother–father dyads resulting in 340 mothers and 152 fathers; about half were non-Hispanic white. Mothers and fathers completed a 14-item SPS-I for their 12-month-old infant. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to explore and validate SPS-I's underlying structure. Multigroup CFA was used to examine measurement invariance across mothers and fathers. Reliability was examined using Cronbach's alpha. Concurrent validity was assessed using linear regressions examining associations between SPS-I factors and parent-reported infants nighttime sleep duration. Convergent validity was assessed using paired-sample t -tests to test whether the SPS-I subscale scores were similar between mothers and fathers in the same household. EFA and CFA confirmed a 3-factor, 12-item model: sleep routines, sleep autonomy, and screen media in the sleep environment. SPS-I was invariant across mothers and fathers and was reliable. Concurrent and convergent validity were established. SPS-I has good psychometric properties, supporting its use for characterizing sleep routines, sleep autonomy, and screen media in the sleep environment by mothers and fathers. Supplemental data for this article is available online at https://doi.org/10.1080/08964289.2021.2002799 .